The Influence of Selected Gastrointestinal Parasites on Apoptosis in Intestinal Epithelial Cells - Patrycja Kapczuk; Danuta Kosik-Bogacka; Patrycja Kupnicka; Emilia Metryka; Donata Simińska; Karolina Rogulska; Marta Skórka-Majewicz; Izabela Gutowska; Dariusz Chlubek; Irena Baranowska-Bosiacka (Biomolecules, 2020)
Studies on the parasite–host interaction may provide valuable information concerning the modulation of molecular mechanisms as well as of the host immune system during infection. To date, it has been demonstrated that intestinal parasites may affect, among others, the processes of digestion in the gastrointestinal system of the host, thus limiting the elimination of the parasite, the immune response as well as inflammation. However, the most recent studies suggest that intestinal parasites may also affect modulation of the apoptosis pathway of the host. The present paper presents the latest scientific information on the influence of intestinal parasite species (Blastocystis sp., Giardia sp., Cryptosporidium sp., Trichuris sp., Entamoeba histolytica, Nippostrongylus brasiliensis, Heligmosomoides polygyrus) on the molecular mechanisms of apoptosis in intestinal epithelial cells. This paper stresses that the interdependency between the intestinal parasite and the host results from the direct effect of the parasite and the host’s defense reactions, which lead to modulation of the apoptosis pathways (intrinsic and extrinsic). Moreover, the present paper presents the role of proteins involved in the mechanisms of apoptosis as well as the physiological role of apoptosis in the host’s intestinal epithelial cells.